552: The impact of the COVID-19 pandemic on MRSA pneumonia admissions: a national inpatient study - El Labban, Mohamad (2024)
Introduction: The COVID-19 pandemic was officially declared in the United States by the Centers for disease control and prevention (CDC) on January 5, 2020. Methicillin-resistant Staphylococcus aureus (MRSA) can cause post-viral pneumonia. We wanted to study the impact of the pandemic on patients admitted with MRSA pneumonia. Methods: Using the National Inpatient Sample Database 2017 to 2020, we conducted a retrospective study of adult patients admitted with MRSA pneumonia according to ICD-10 codes. Several demographics and comorbidities were analyzed. Chi square analysis and two sample t-test were used for statistical analysis, p value < 0.05 was considered significant. Results: Patients were studied in two categories by year: 2017-2019 vs. 2020 admissions. MRSA pneumonia admissions in 2020 (5545) were less than in 2017 (6270), 2018 (8635) and 2019 (7485). Both groups had similar baseline patient characteristics, 50% were females, around 80% were Caucasian white, and the mean age was around 66 years. The percentage of patients with a Carlson Comorbidity Index score of 3 or more was around 52% in both groups, p-value 0.75. Statistically significant comorbidities noticed in the 2020 group included cigarette smoking (16% vs. 12%), supraventricular tachycardia (30% vs. 23%), obesity (20% vs. 16.7%), and chronic kidney disease (18% vs. 15%) (all had a p value less than 0.05). Mortality was higher in the 2020 group (365 (6.5%) vs. 2017 (355, 5.6%), 2018 (415, 4.8%), and 2019 (400, 5.3%) however not statistically significant among the two groups (6.5% vs. 5.2%, p-value 0.07). Rates of septic shock were higher in the 2020 group (165 (3%) vs. 2017 (125, 2%), 2018 (140, 1.6%), and 2019 (145, 1.9%) (3% vs. 1.8%, p-value 0.01). Rates of mechanical ventilation were higher in the 2020 group (850 (15.3%) vs. 2017 (725, 11.5%), 2018 (1050, 12.1%), and 2019 (815, 10.8%) (15.3% vs. 11.5%, p value < 0.01). The mean length of stay was higher in the 2020 group (9.9 days vs. 2017 (8.89 days), 2018 (8.91 days), and 2019 (8.94 days). The mean admission total charge was higher in the 2020 group (105792 $ vs. 2017 (78516$), 2018 (83538$), and 2019 (91031$). Conclusions: The patients across the 4 years had similar baseline epidemiological and clinical (comorbid) characteristics and yet, patients admitted in 2020 had worse outcomes.